Decision support system : development and application using off-the-shelf application packages and microcomputer in a manufacturing company : a thesis presented in fulfilment of the requirements for the degree of Master of Philosophy in Production and Quality at Massey University - Tan, Sin Week (Massey University, 1986)
The aim of this research was to apply the decision support systems and quality costs concepts to build a Quality Costs Management Information System/Decision Support System (QC MIS/DSS) using off-the-shelf application packages and a microcomputer for the system development. To achieve these aims, a survey was conducted to find out the extent of computer applications in industries in the Manawatu region. Application packages were evaluated to select two suitable packages for the development of a QC MIS/DSS project in Company A. A survey on the application of computers in the Manawatu region showed that about 47.4% of respondents were using microcomputers. The majority of the respondents used computer programs for finance, invoicing and stock control. Decision support was not yet a major usage. The Prototype of QC MIS/DSS has the features of easy to use, simple to understand, user controlled, adaptive and easy to communicate with. The mangers/ users were satisfied with the prototype demonstrated. Interest in the possibility of expanding the system to other existing products and for detailed information on quality costs were raised. Two main factors which contributed to the success of the project were - the prototyping approach used for system development. - the management support during the system development process. - the software used. There were some significant changes after the concept of QC MIS/DSS was introduced to Company A which included improvement on data collection and records for rework, rejects, scraps on the assembly line, increasing the awareness of the quality costs and their significance, as well as the process efficiency, As a result, work study and time study were carried out on the assembly line. The project has met the predetermined objectives and the users' requirements. It has also proved that it is feasible to apply the decision sypport system theories and prototyping system development methodology by using the costs and time saving tools- Application packages for their model building. To further improve and enhance the effectiveness of the system, it would be very useful to develop the DSS to a semi-expert system which would provide users with warning and some guidelines on what actions to be taken. This could be used as a consultancy device which would further improve the efficiency of the managers and decision makers in decision making.
Keywords: Decision support systems; Management information systems; Business -- Data processing